Degradation and Corrosion of Biodegradable Metal Zn-xCa - Supardi, Adri; Afifah, Miftachul Nur; Rudyardjo, Djony Izak (Universitas Airlangga, 2020)
Zn-based biodegradable metals (BMs) are considered as new potential in osteosynthetic implant devices. In this study Ca, which acts as an essential element in the human body, is used to improve the rate of Zn degradation and corrosion. The alloy was synthesized using the powder metallurgy method with two different processes: cold pressing followed by sintering (CP-S) and hot isostatic pressing (HIP). Microstructure properties, as well as in vitro degradation and corrosion were studied to determine the effect of adding Ca. Variations in the sample consist of Zn-0.5Ca, Zn-1Ca, Zn-1.5Ca and Zn-2Ca. The results and analysis of test data show that the addition of Ca increases the rate of corrosion and degradation of the materials. Better bonding and microstructure properties are obtained in Zn-2Ca samples which form CaZn13 phases and small porosity. As for the HIP process, a better microstructure is obtained compared to CP-S.